Ethnobotanical inventory and evaluation of the medicinal virtues of traditional plants of Djelfa (central Algeria) - Bounab, Souhila; Badraoui, Yahia; Brahimi, Hibat-Allah; Dali, Zahia (Ethnobotany Research and Applications, 2026)
Background: Medicinal plants are an essential part of natural and cultural heritage, playing a fundamental role in traditional health systems, particularly in developing countries where they are often the main therapeutic resource available to rural populations. Objective: This floristic and ethnobotanical study was conducted with the aim of compiling the most comprehensive inventory possible of medicinal plants and gathering as much information as possible on therapeutic practices in the Djelfa region in central Algeria. Methods: Relying on a semi-structured questionnaire and a stratified random sampling method, a total of 120 local informants were interviewed. The data obtained was processed using quantitative tools specific to ethnobotany in order to better understand the relative importance of the species surveyed. Results: The survey identified 105 medicinal species distributed across 86 genera and 34 botanical families, with the most represented being the Lamiaceae (11 species) and Asteraceae (7 species), with a marked preference for infusion (34.28%), leaves (25.71%), flowers (15.23%), and fruits (14.28%) as methods of preparation. Conclusions: The results obtained provide a valuable basis for the enhancement of local traditional pharmacopeia and highlight the potential of these plant resources within the framework of sustainable development strategies and the promotion of traditional medicine in Algerian rural areas. Keywords: Ethnobotanical study, Inventory, Traditional medicine, Djelfa, Algeria.